SYNTAX ORGANIZATION OF VASYL STEFANIK’S NOVELLAS: POETICS OF GRAMMATICAL STRUCTURES - Betsenko, T. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is an attempt to describe the style and stylistic dominant artistic style novelist. Attention is focused on the analysis of the syntactic organization of the artist’s words. A review of the key features specific to the syntax of short stories writer. It settled in general stylistic potential of syntactic structures in the author’s works.